أثر التمكين الإداري على الأداء الوظيفي دراسة حالة - • بن سهيل مريم (جامعة المسيلة, 2020)
هدفت هذه الدراسة الى تحليل اثر التمكين على الأداء الوظيفي لدى العاملين. و قد توصلت إلى أن التمكين يدفع العامل نحو التقدم و التطور الوظيفي و يتطلب استراتيجية خاصة بالمنظمة تنطلق من اهميته تأخذ بعين الاعتبار اهم مراحله و نماذجه و اعباءه و معوقاته. كما تم التوصل الى ان الاداء الوظيفي يلعب دورا هاما و حيويا بحث تشكل عناصره الظروف المناسبة للعاملين ليكونوا اكثر ابداعا و مبادرة و كفاءة. -و تجمع العديد من الدراسات التي تم الاطلاع عليها على العلاقة الارتباطية و التأثيرية بالتمكين و الأداء الوظيفي -و تدعو إلى ضرورة سعي المؤسسة إلى تعزيز التمكين من خلال التركيز على منحهم قدرا اكبر من الحرية و الاستقلالية. -على تحسين نظم التفويض و المشاركة و التحفيز و التشجيع داخل المؤسسة العمل. -ضرورة اهتمام المؤسسة بتنمية و تطوير الأداء الوظيفي من خلال تبني إستراتيجية خاصة تأخذ بعين الاعتبار اغلب العوامل المؤثرة عليه و التي تعتبر تمكين العاملين من أهم مداخلها Summary: This study aimed to analyze the effect of empowerment on employee performance. And I have concluded that empowerment drives the worker towards career advancement and development and requires a special strategy for the organization that stems from its importance and takes into account its most important stages, models, burdens and obstacles. It was also concluded that job performance plays an important and vital role, the elements of which constitute the appropriate conditions for workers to be more creative, initiative and efficient. - Many of the studies that have been viewed combine the correlational and influential relationship between empowerment and job performance - And calls for the need for the Foundation to seek to enhanceempowerment by focusing on giving them greater freedom andindependence. - On improving the systems of delegation, participation,motivation and encouragement within the organization. - The need for the institution to focus on developing and developing job performance by adopting a special strategy that takes into account most of the factors affecting it and which considers empowering workers as one of its most important approaches